2009
DOI: 10.1074/jbc.m109.012484
|View full text |Cite
|
Sign up to set email alerts
|

NDRG4 Is Required for Cell Cycle Progression and Survival in Glioblastoma Cells

Abstract: NDRG4 is a largely unstudied member of the predominantly tumor suppressive N-Myc downstream-regulated gene (NDRG) family. Unlike its family members NDRG1-3, which are ubiquitously expressed, NDRG4 is expressed almost exclusively in the heart and brain. Given this tissue-specific expression pattern and the established tumor suppressive roles of the NDRG family in regulating cellular proliferation, we investigated the cellular and biochemical functions of NDRG4 in the context of astrocytes and glioblastoma multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 53 publications
(55 reference statements)
1
48
2
Order By: Relevance
“…However, NDRG3 could serve as a tumor promoter for prostate cancer PC3 cell line because overexpression of NDRG3 increased cell growth and migration capability of PC3 cells ). We showed that NDRG4's expression was downregulated at both RNA and protein levels in GBM tissues compared to normal brain tissues, which is in conflict with the findings by Schilling et al (2009), who showed that NDRG4 is upregulated in GBM compared to human cortex tissues and that knocking down of NDRG4 reduced the cell viability of GBM cells. The discrepancies could be due to several possible reasons.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, NDRG3 could serve as a tumor promoter for prostate cancer PC3 cell line because overexpression of NDRG3 increased cell growth and migration capability of PC3 cells ). We showed that NDRG4's expression was downregulated at both RNA and protein levels in GBM tissues compared to normal brain tissues, which is in conflict with the findings by Schilling et al (2009), who showed that NDRG4 is upregulated in GBM compared to human cortex tissues and that knocking down of NDRG4 reduced the cell viability of GBM cells. The discrepancies could be due to several possible reasons.…”
Section: Discussioncontrasting
confidence: 56%
“…The discrepancies could be due to several possible reasons. In the report by Schilling et al (2009), the realtime PCR of NDRG4 was performed by comparing normal primary human astrocytes (NHA 1 and 2) and cultured cells derived from three human GBM xenograft samples (Schilling et al, 2009), whereas in the TCGA as well as in our data (Fig 1 and Supplementary Table 1), the analysis was performed by comparing human GBM tissues with normal brain tissues. The sample size (three cases of GBM) was also very small in Schilling's case but quite large (410 TCGA GBM samples and 49 GBM samples from our laboratory).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fax: 81-6-6835-1176; E-mail: kame@ri.ncvc.go.jp. 2 To whom correspondence may be addressed: 5-7-1 Fujishirodai, Suita, Osaka 565-8565, Japan. Fax: 81-6-6835-6894; E-mail: hyanamot@ res.ncvc.go.jp.…”
Section: N-myc Downstream-regulated Gene (Ndrg)mentioning
confidence: 99%
“…Furthermore, accumulating evidence implicates their roles in development, cancer metastasis, and the immune system (1)(2)(3)(4)(5).…”
Section: N-myc Downstream-regulated Gene (Ndrg)mentioning
confidence: 99%